Perspectives on the implementation of p henomenology on pre linguistic communication - Casallo, Víctor (2016)
Phenomenology systematically clarifies the structures and processes that make possible different experiences of communication based on pre linguistic foundation. This article explores this perspective and argues that it allows a deeper comprehension of experiences of personal and social reintegration through the interaction with animals of inmates and children with autism. Also, this article follows the thesis of David Abram: that the re discovery of the amplitude od the communicational possibilities in the human beings opens up alternatives of solution to the cultural discomforts that are growing deep in contemporary urban cultures of the world.